2018
DOI: 10.1002/slct.201801516
|View full text |Cite
|
Sign up to set email alerts
|

KA2‐Coupling Reaction Catalyzed by Semi‐Heterogeneous Magnetically Graphene Oxide Supported Copper Catalyst under Microwave Condition

Abstract: Functional Schiff base chelating groups (PCA) were covalently grafted onto the surface of magnetic graphene oxide (GO‐Fe3O4) via a facile silanization reaction under mild condition. The obtained GO‐Fe3O4‐PCA was further chelated with CuCl2 as an efficient, robust, and recyclable semi‐heterogeneous catalyst (GO‐Fe3O4‐CuCl2) for one‐pot three‐component KA2 coupling of ketones, amines, and alkynes. It exhibited environmentally benign, excellent magnetic separation performance, and higher catalytic activity than o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Some leading examples include the use of Cu 2 O nanoparticles on titania, [69] nano Cu 2 O-ZnO, [70] Cu 2 O/nano-CuFe 2 O 4 , [71] CuO/Fe 2 O 3 nanoparticles, [72] Cu(II)-hydromagnesite, [73] polystyrene-supported, N-phenylpiperazine-CuBr 2 , and highly active, polymer-supported bipyridine-CuBr 2 , [74] Cu(II) @furfural imine-decorated Halloysite, [75] CuI on Amberlyst A-21, [76] as well as semi-heterogeneous, magnetically recoverable graphene oxide-supported CuCl 2. [77] Catalytic systems based on other metals have been also developed, such as Ag-doped nanomagnetic γ-Fe 2 O 3 @DA core-shell hollow spheres, [78] Fe 2 O 3 @SiO 2 -IL/Ag hollow spheres, [79] and polystyrene-supported N-heterocyclic carbene-Au(III). [80] More recently, our research group reported a robust catalytic system for the KA 2 reaction, introducing Zn (OAc) 2 as a reliable catalyst under neat conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Some leading examples include the use of Cu 2 O nanoparticles on titania, [69] nano Cu 2 O-ZnO, [70] Cu 2 O/nano-CuFe 2 O 4 , [71] CuO/Fe 2 O 3 nanoparticles, [72] Cu(II)-hydromagnesite, [73] polystyrene-supported, N-phenylpiperazine-CuBr 2 , and highly active, polymer-supported bipyridine-CuBr 2 , [74] Cu(II) @furfural imine-decorated Halloysite, [75] CuI on Amberlyst A-21, [76] as well as semi-heterogeneous, magnetically recoverable graphene oxide-supported CuCl 2. [77] Catalytic systems based on other metals have been also developed, such as Ag-doped nanomagnetic γ-Fe 2 O 3 @DA core-shell hollow spheres, [78] Fe 2 O 3 @SiO 2 -IL/Ag hollow spheres, [79] and polystyrene-supported N-heterocyclic carbene-Au(III). [80] More recently, our research group reported a robust catalytic system for the KA 2 reaction, introducing Zn (OAc) 2 as a reliable catalyst under neat conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Applying MGO supported copper catalyst (GO–Fe 3 O 4 –CuCl 2 ) is another example of practicable method of using semi‐heterogeneous catalysts for propargyl amine synthesis. [ 104 ] Low chemical reactivity of ketones compared with aldehydes encouraged their investigation for the preparation of propargyl amines through KA 2 coupling reaction of ketones, amines, and alkynes under MW irradiation. GO–Fe 3 O 4 –CuCl 2 possessed advantages of homogeneous (good efficiency and selectivity) and heterogeneous (recyclability) catalyst, which make it as an efficient semi‐heterogeneous catalyst for the synthesis of propargyl amines in moderate to excellent yields under mild reaction conditions.…”
Section: Application Of Copper Modified Graphene Oxide Catalysts For Carbon‐nitrogen Bond Formationmentioning
confidence: 99%
“…One way to form the propargylamines is to apply the transition‐metal catalysts in three‐component coupling of aldehydes or ketones, amines, and alkynes (A 3 ‐coupling or KA 2 ‐coupling reaction). However, the KA 2 reaction has been largely underdeveloped because of the extremely lower reactivity of ketones …”
Section: Introductionmentioning
confidence: 99%